مـعوقـــــات المؤسســـات الصغــیرة والمتــوسطـــــة فــي الجـزائـــــر - دریس , أمیرة; دریس , بشرى (Finance and Business Economies Review, 2017)
Entrepreneurship has become a concept widely used and traded extensively, as are currently defined as an area of research, due to its growing importance, became both the government and university researchers and society in general, they are more interested in the evolution of the contractors and their institutions, and their ability to survive and wildebeest. It can explain this growing interest because of the provided by these contractors and new institutions (which are often small and medium enterprises) of job opportunities and support for sustainable development, but these small and medium enterprises face a lot of obstacles that in front of developed and promoted.